KEDUDUKAN KETERANGAN AHLI HUKUM DALAM PROSES PENYIDIKAN DI KEPOLISIAN DAERAH RIAU - Lylis Suryani br. Sinaga; Erdianto '; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Examination of a case in a judicial process aimed at finding the material truth. There is an interesting tendency to be studied in the practice of law enforcement in Indonesia. The role of expert testimony increasingly prominent and there are quite a lot of cases the use of expert testimony as a justification in deciding criminal cases. as stipulated in Law No. 8 of 1981 on the Code of Criminal Procedure (Code of Criminal Procedure) in Article 184 paragraph (1). According to Article 184 paragraph (1) Code of Criminal Procedure states that legal evidence is witness' testimony, expert Specification, Letters, Help, Information defendant. The research objective of this thesis are: First, to determine the position of expert testimony in the investigation process in Riau Regional Police, Second, to determine the criteria for someone to be called the lawyer who requested the expert testimony in practice in Riau Regional Police, Third, to know the power of information legal experts in the investigation process until the judge ruled.From the research, there are three main issues that can be inferred. First, Position description lawyers in Riau Regional Police investigation process, have an important role to help the investigator to search and collect evidence in the search for truth usahannya material a criminal case, the Second, someone criteria to be called a lawyer who requested the expert testimony in practice in Riau Regional Police is someone who has experience in providing expert information and education that has the title of Professor, Doctor or Magester Law from the State University or the University of Private as Riau Regional Police itself has to cooperate with the aim to facilitate bringing a debirokrasi lawyers, Third, expert testimony actually have the power and important role in contributing to the clarity of the completion of a criminal case and help uncover or make light of a criminal case being examined. Suggestions Author, First, it is expected that law enforcement officers should refer to evidence or proof system and verification process that has been regulated by law, second, expert presented at the stage of investigation and in the trial must have the scientific expertise and integrity , independent, and professionalism in order to provide quality information and it should be in the set criteria person called as a legal expert, Third, an expert opinion is presented on the stage of the investigation and the court order may be a more important consideration by the judge in deciding a case.Keywords: Positions, Description Experts, Investigation